Developm ent of carboxymethylcellulose from nata de coco - Lydia S. Manguiat; Veronica C. Sabularse, and; Dario C. Sabularse Sabularse (ASEAN Journal on Science and Technology for Development, 2001)
Nata de coco was used as raw material for the preparation of food-grade carboxymethylcellulose referred to as carboxymethyl-nata (CMN). The effect of various conditions in the carboxymethylation of nata cellulose was determined. The concentration of NaOH, mercerisation time, shredding time during mercerisation and etherification, and the concentration of monochloroacetic acid significantly affected the following physico-chemical properties of CMN, namely, degree of substitution (DS), viscosity, degree of polymerisation (DP), and solubility. The best processing conditions were: the use of 40% NaOH, 60 mins mercerisation time, 60 mins shredding time during mercerisation and etherification, and J.35g/mL ClCH COOH. CMN with desirable properties wasproduced using these conditions.